Acrylic polymer, composition containing same, and preparation method thereof
By using a combination of acrylic polymer and ceramic powder, the problems of complex composition and production process in the prior art are solved, and simplified preparation of ceramic slurry and the acquisition of high-performance coated base films are achieved.
Patent Information
- Application Number
- CN202410507863.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the ceramic composition used in high-temperature lithium batteries has complex compositions, and the preparation process is complex and the cost is high.
The acrylic polymer and ceramic powder are used as the composition of a ceramic slurry for lithium batteries. The acrylic polymer is prepared by polymerization reaction, and mixed with the ceramic powder as the surface material of the coated base film.
The simplified preparation process of ceramic slurry is realized, the cost is reduced, and the peel strength and heat resistance of the coated base film are improved, avoiding the adverse effects of high molecular weight materials on electrical properties.
Smart Images

Figure BDA0004810820430000161 
Figure BDA0004810820430000171 
Figure FDA0004810820420000011
Abstract
Description
Technical Field
[0001] The present invention relates to an acrylic polymer, a composition containing the acrylic polymer and a preparation method thereof. Background Art
[0002] The melting temperature of PP / PE separators for lithium batteries is about 150°C. The melting of the separator will cause the circuit to be disconnected and cause thermal runaway. Heat accumulation will cause the battery to burn or explode, posing a huge safety hazard. Traditional ceramic slurry is composed of ceramic powder, thickener, dispersant, binder, wetting agent and defoamer, which is coated on the surface of the base film to improve the heat resistance of the separator. The preparation process of traditional ceramic slurry is relatively complicated and costly. Summary of the invention
[0003] The technical problem to be solved by the present invention is that the ceramic composition used for high temperature resistant lithium batteries in the prior art has complex components. To this end, the present invention provides an acrylic polymer, a composition containing the same and a preparation method thereof. The acrylic polymer and ceramic powder are used as ceramic slurry for lithium batteries to coat the surface of the base film, which has good peel strength and heat resistance, and also reduces the use of polymer materials in the ceramic slurry, avoiding the adverse effect of high molecular weight materials on electrical properties caused by free electrolyte.
[0004] The present invention provides an acrylic polymer, which is composed of a first type of structural unit, a second type of structural unit and a third type of structural unit;
[0005] The first type of structural unit is selected from One or more of;
[0006] The second type of structural unit is selected from One or more of;
[0007] The third type of structural unit is selected from One or more of;
[0008] R 1 , R 2 , R 3 and R 4 are independently -OH, -OLi, -ONa, -OK, -ONH4 or And not OH at the same time;
[0009] Taking the total molar number of the first structural unit, the second structural unit and the third structural unit as 100%, in the acrylic polymer, the molar percentage of the first structural unit is 5%-85%, the molar percentage of the second structural unit is 4%-85%; and the molar percentage of the third structural unit is 2%-15%;
[0010] The weight average molecular weight of the acrylic polymer is 100,000-800,000 g / mol;
[0011] The acrylic polymer is a random copolymer.
[0012] In a preferred embodiment, R 1 , R 2 , R 3 and R 4 are independently -OH, ONa or -ONH4.
[0013] In a preferred embodiment, in the first type of structural unit, the substituent R 1 , R 2 , R 3 and R 4 The total molar number is calculated as 100%, R 1 , R 2 , R 3 and R 4 The mole percentage of -OH in the is 0-20%; for example 0 or 20%.
[0014] In a preferred embodiment, the molar percentage of the first type of structural units is 8%-83%, for example, 8%, 9%, 60%, 70% or 83%.
[0015] In a preferred embodiment, the first type of structural unit is or by Composition, R 1 is -ONa or -ONH4; R 2 It is -OH, -ONa or -ONH4.
[0016] In a preferred embodiment, the first type of structural unit is composed of Composition, R 1 and R 2 At the same time, it is -ONa or -ONH4; The molar ratio is (0.1-3):1, such as 0.25:1, 2.3:1 or 2.5:1; for example, the first type of structural unit is composed of composition.
[0017] In a preferred embodiment, the first type of structural unit is R 2 is -OH, -ONa or -ONH4, for example, the first type of structural unit is or by composition, The molar ratio is 1:4.
[0018] In a preferred embodiment, the molar percentage of the second type of structural units is 5%-81%, for example, 5%, 20%, 36%, 78% or 81%.
[0019] In a preferred embodiment, the second structural unit is or by composition.
[0020] In a preferred embodiment, the second structural unit is composed of Composition, the The molar ratio is (1-3):1, for example 2:1.
[0021] In a preferred embodiment, the molar percentage of the third type of structural units is 4%-13%, for example, 4%, 10%, 11%, 12% or 13%.
[0022] In a preferred embodiment, the third type of structural unit is or by composition.
[0023] In a preferred embodiment, the third type of structural unit is Composition, the The molar ratio is (1-3):1, for example 2.5:1.
[0024] In a preferred embodiment, the weight average molecular weight of the acrylic polymer is 150,000 g / mol, 270,000 g / mol, 440,000 g / mol, 620,000 g / mol or 740,000 g / mol.
[0025] In a preferred embodiment, the glass transition temperature of the acrylic polymer is 60-150°C, such as 65°C, 81°C, 112°C, 120°C or 143°C.
[0026] In a preferred embodiment, the acrylic polymer is weakly alkaline, and its pH value is 7-9, such as 7-8.5.
[0027] In a preferred embodiment, the structural unit is selected from any of the following embodiments:
[0028] Scheme 1: The structural unit is composed of the following molar percentages of structural units: 83% of the first structural unit, 5% of the second structural unit and 12% of the third structural unit;
[0029] The first type of structural unit is composed of Composition, the The molar ratio is 2.3:1; the second structural unit is The third type of structural unit is composed of Composition, the The molar ratio is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C and the weight average molecular weight is 150,000 g / mol;
[0030] Scheme 2: The structural unit is composed of the following molar percentages of structural units: 70% of the first structural unit, 20% of the second structural unit and 10% of the third structural unit;
[0031] The first type of structural unit is composed of Composition, the The molar ratio is 2.5:1; the second structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 65°C and a weight average molecular weight of 270,000 g / mol;
[0032] Scheme 3: The structural unit is composed of the following molar percentages of structural units: 60% of the first structural unit, 36% of the second structural unit and 4% of the third structural unit;
[0033] The first type of structural unit is composed of Composition, the The molar ratio is 0.25:1; the second structural unit is composed of Composition, the The molar ratio is 2:1; the third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 81°C and a weight average molecular weight of 440,000 g / mol;
[0034] Scheme 4: The structural unit is composed of the following molar percentages of structural units: 8% of the first structural unit, 81% of the second structural unit and 11% of the third structural unit;
[0035] The first type of structural unit is composed of composition, The molar ratio is 1:4; the second structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 120°C and a weight average molecular weight of 620,000 g / mol;
[0036] Scheme 5: The structural unit is composed of the following mole percentages of structural units: 9% of the first structural unit, 78% of the second structural unit and 13% of the third structural unit;
[0037] The first type of structural unit is The second type of structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 143° C. and a weight average molecular weight of 740,000 g / mol.
[0038] The present invention provides an acrylic polymer, which is prepared by the following polymerization method, which comprises the following steps: in a solvent, in the presence of an initiator, polymerizing a polymerizable monomer to obtain the acrylic polymer;
[0039] The polymerizable monomers include 5%-85% of a first polymerizable monomer, 4%-85% of a second polymerizable monomer, and 2%-15% of a third polymerizable monomer, wherein the percentages are respectively the molar percentages of the molar number of the first polymerizable monomer, the second polymerizable monomer, or the third polymerizable monomer to the total molar number of each polymerizable monomer of the acrylic polymer,
[0040] The first type of polymerizable monomer is selected from One or more of R 1 , R 2 , R 3 and R 4 are independently -OH, -OLi, -ONa, -OK, -ONH4 or And not OH at the same time;
[0041] The second type of polymerizable monomer is selected from one or more of methyl methacrylate, ethyl acrylate, butyl acrylate, ethyl methacrylate, cyclohexyl methacrylate and acrylonitrile;
[0042] The third type of polymerizable monomer is selected from one or more of hydroxymethyl acrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate;
[0043] The weight average molecular weight of the acrylic polymer is 100,000-800,000 g / mol;
[0044] The acrylic polymer is a random copolymer.
[0045] In a preferred embodiment, the first type of polymerizable monomers has a substituent R 1 , R 2 , R 3 and R 4 The total molar number is calculated as 100%, R 1 , R 2 , R 3 and R 4The molar percentage of -OH in the monomer is 0-20%; for example, 0 or 20%; in the first type of polymerizable monomer, when R 1 , R 2 , R 3 and R 4 When the molar percentage of -OH in the reaction is greater than 80%, the polymerization reaction further comprises the following post-treatment steps: neutralization; the alkaline substance used for neutralization can be ammonia or sodium hydroxide.
[0046] In a preferred embodiment, R 1 , R 2 , R 3 and R 4 are independently -OH, ONa or -ONH4.
[0047] In a preferred embodiment, the first type of polymerizable monomer is and / or R 1 is -ONa or -ONH4; R 2 It is -OH, -ONa or -ONH4.
[0048] In a preferred embodiment, the first type of polymerizable monomer is The composition of R 1 and R 2 At the same time, it is -ONa or -ONH4; The molar ratio is (0.1-3):1, such as 0.25:1, 2.3:1 or 2.5:1; for example, the first type of structural unit is composed of ammonium acrylate and ammonium methacrylate or of sodium acrylate and sodium methacrylate.
[0049] In a preferred embodiment, the first type of polymerizable monomer is R 2 It is -OH, -ONa or -ONH4, for example, the first type of structural unit is sodium methacrylate or consists of methacrylic acid and sodium methacrylate, and the molar ratio of methacrylic acid to sodium methacrylate is 1:4.
[0050] In a preferred embodiment, the molar percentage of the first type of polymerizable monomer is 8%-83%, for example, 8%, 9%, 60%, 70% or 83%.
[0051] In a preferred embodiment, the mass percentage of the first type of polymerizable monomers is 6.98%, 7.89%, 51.75%, 61.31% or 78.16%.
[0052] In a preferred embodiment, the second type of polymerizable monomer is methyl methacrylate, ethyl acrylate, or consists of methyl methacrylate and ethyl acrylate.
[0053] In a preferred embodiment, the second type of polymerizable monomers consists of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is (1-3):1, for example, 2:1.
[0054] In a preferred embodiment, the molar percentage of the second type of polymerizable monomer is 5%-81%, for example, 5%, 20%, 36%, 78% or 81%.
[0055] In a preferred embodiment, the second type of polymerizable monomers consists of methyl methacrylate and ethyl acrylate, and the mass ratio of methyl methacrylate to ethyl acrylate is (1-3):1, for example, 2.2:1.
[0056] In a preferred embodiment, the mass percentage of the second type of polymerizable monomers is 6.34%, 23.26%, 41.4%, 78.95% or 81.4%.
[0057] In a preferred embodiment, the third type of polymerizable monomer is hydroxypropyl methacrylate, hydroxyethyl acrylate, hydroxymethyl acrylamide, or is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate.
[0058] In a preferred embodiment, the third type of polymerizable monomers consists of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is (1-3):1, for example, 2.5:1.
[0059] In a preferred embodiment, the molar percentage of the third type of polymerizable monomer is 5%-25%, for example, 6.86%, 11.63%, 13.16%, 15.42% or 15.5%.
[0060] In a preferred embodiment, the third type of polymerizable monomers consists of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the mass ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is (1-3):1, for example, 2.1:1.
[0061] In a preferred embodiment, the mass percentage of the third type of polymerizable monomer is 5%-25%, for example, 6.86%, 11.63%, 13.16%, 15.42% or 15.5%.
[0062] In a preferred embodiment, the polymerized monomers of the acrylic polymer are composed of the following molar percentages of polymerized monomers: 5%-85% of the first type of polymerized monomers, 4%-85% of the second type of polymerized monomers and 2%-15% of the third type of polymerized monomers, and the types of the first type of polymerized monomers, the second type of polymerized monomers and the third type of polymerized monomers are as described in any of the previous items.
[0063] In a preferred embodiment, the weight average molecular weight of the acrylic polymer is 150,000-740,000 g / mol, for example, 150,000 g / mol, 270,000 g / mol, 440,000 g / mol, 620,000 g / mol or 740,000 g / mol.
[0064] In a preferred embodiment, the glass transition temperature of the acrylic polymer is 60-150°C, such as 65°C, 81°C, 112°C, 120°C or 143°C.
[0065] Scheme 1: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 83% of the first type of polymerizable monomers, 5% of the second type of polymerizable monomers, and 12% of the third type of polymerizable monomers;
[0066] The first type of polymerizable monomers is composed of ammonium acrylate and ammonium methacrylate, and the molar ratio of ammonium acrylate to ammonium methacrylate is 2.3:1; the second type of polymerizable monomers is methyl methacrylate; the third type of polymerizable monomers is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C, and the weight average molecular weight is 150,000 g / mol;
[0067] Scheme 2: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 70% of the first type of polymerizable monomers, 20% of the second type of polymerizable monomers and 10% of the third type of polymerizable monomers;
[0068] The first type of polymerizable monomer is composed of ammonium acrylate and ammonium methacrylate, and the molar ratio of ammonium acrylate to ammonium methacrylate is 2.5:1; the second type of polymerizable monomer is ethyl acrylate; the third type of polymerizable monomer is hydroxypropyl methacrylate; preferably, the glass transition temperature of the acrylic polymer is 65°C, and the weight average molecular weight is 270,000 g / mol;
[0069] Scheme 3: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 60% of the first type of polymerizable monomers, 36% of the second type of polymerizable monomers, and 4% of the third type of polymerizable monomers;
[0070] The first type of polymerizable monomers is composed of sodium acrylate and sodium methacrylate, and the molar ratio of sodium acrylate to sodium methacrylate is 0.25:1; the second type of polymerizable monomers is composed of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is 2:1; the third type of polymerizable monomer is hydroxyethyl acrylate; preferably, the glass transition temperature of the acrylic polymer is 81°C and the weight average molecular weight is 440,000 g / mol;
[0071] Scheme 4: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 8% of the first type of polymerizable monomers, 81% of the second type of polymerizable monomers, and 11% of the third type of polymerizable monomers;
[0072] The first type of polymerizable monomer is composed of methacrylic acid and sodium methacrylate, and the molar ratio of methacrylic acid to sodium methacrylate is 1:4; the second type of polymerizable monomer is methyl methacrylate; the third type of polymerizable monomer is hydroxyethyl acrylate; preferably, the glass transition temperature of the acrylic polymer is 120°C, and the weight average molecular weight is 620,000 g / mol;
[0073] Scheme 5: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 9% of the first polymerizable monomer, 78% of the second polymerizable monomer, and 13% of the third polymerizable monomer;
[0074] The first type of polymerizable monomer is sodium methacrylate; the second type of polymerizable monomer is methyl methacrylate; the third type of polymerizable monomer is hydroxymethyl acrylamide; preferably, the glass transition temperature of the acrylic polymer is 143°C and the weight average molecular weight is 740,000 g / mol.
[0075] In a preferred embodiment, the polymerizable monomer and part of the solvent are used in the form of a polymerizable monomer solution, and the mass percentage of the polymerizable monomer in the polymerizable monomer solution may be 40%-90%, for example, 46%, 50%, 84% or 88%.
[0076] In a preferred embodiment, the solvent is water, such as deionized water.
[0077] The amount of the solvent used is the conventional amount used in this type of reaction, and is preferably not to affect the progress of this type of reaction. In a preferred embodiment, in the polymerization reaction, the mass ratio of the solvent to the polymerization monomer is (2-5):1, for example, 3:1, 3.2:1, 3.4:1, 3.7:1 or 3.9:1.
[0078] The initiator is a conventional initiator for such reactions in the art. In a preferred embodiment, the initiator is selected from one or more of ammonium persulfate, sodium persulfate and a redox system consisting of vitamin C and sodium persulfate; for example, ammonium persulfate.
[0079] In a preferred embodiment, the mass ratio of the initiator to the polymerization monomer is (0.01-0.05):1, for example, 0.012:1, 0.013:1, 0.015:1, 0.02:1 or 0.028:1.
[0080] In a preferred embodiment, the initiator and part of the solvent are used in the form of an initiator solution, and the mass percentage of the initiator in the initiator solution may be 1%-10%, such as 2%, 3%, 4% or 6%.
[0081] In a preferred embodiment, the reaction system of the polymerization reaction further comprises a protective colloid, and the protective colloid is selected from one or more of acrylic resin, polyvinyl alcohol and povidone, such as acrylic resin or polyvinyl alcohol.
[0082] In a preferred embodiment, the alcoholysis degree of the polyvinyl alcohol is 80%-90%, for example 88%.
[0083] In a preferred embodiment, the molecular weight of the acrylic resin is 6000-1000 g / mol, and the acid value is 200-230 mgKOH / g.
[0084] In a preferred embodiment, the acrylic resin is methacrylic resin or styrene acrylic resin.
[0085] In a preferred embodiment, the methacrylic resin has a molecular weight of 9500 g / mol and an acid value of 218 mgKOH / g or a molecular weight of 7000 g / mol and an acid value of 218 mgKOH / g; for example, Hanwha soluryl-70 or Hanwha soluryl-90;
[0086] In a preferred embodiment, the molecular weight of the styrene acrylic resin is 8600 g / mol and the acid value is 215 mgKOH / g, such as BASF Joncryl 678.
[0087] In a preferred embodiment, the mass ratio of the protective colloid to the polymerized monomer is (0.1-1):1, for example, 0.13:1, 0.26:1, 0.45:1, 0.52:1 or 0.56:1.
[0088] In a preferred embodiment, the protective colloid is an acrylic resin, and the acrylic resin needs to be neutralized with the alkaline substance to preferably neutralize the acid value; preferably, the acrylic resin and the alkaline substance are added together to the reaction system of the polymerization reaction.
[0089] In a preferred embodiment, the polymerization reaction is divided into a first stage polymerization reaction and a second stage polymerization reaction; preferably, the mass of the polymerization monomer added in the first stage polymerization reaction accounts for 8%-12% of the total mass of the polymerization monomer, for example 9%-11%, and for example 10%; the mass of the initiator added in the first stage polymerization reaction accounts for 8%-12% of the total mass of the initiator, for example 9%-11%, and for example 10%.
[0090] In a preferred embodiment, the polymerization method also includes a method for preparing the first type of polymerization monomer, and the preparation method of the first type of polymerization monomer includes the following steps: in water, an acrylic acid monomer is subjected to a neutralization reaction with an alkaline substance to obtain the first type of polymerization monomer, the acrylic acid monomer is selected from one or more of acrylic acid, methacrylic acid, maleic acid and fumaric acid, and the alkaline substance is selected from one or more of sodium hydroxide, ammonia, monoethanolamine and lithium hydroxide; the molar ratio Z of the alkaline substance to the acrylic acid monomer can be (0.2-5):1, for example (0.2-4):1, for example 0.2:1≤Z<0.8:1 or 0.8:1≤Z≤4:1.
[0091] In a preferred embodiment, the acrylic monomer is acrylic acid, methacrylic acid, or acrylic acid and methacrylic acid. The amount of the acrylic monomer is the same as the amount of the first type of polymerizable monomer.
[0092] In a preferred embodiment, the alkaline substance is sodium hydroxide or ammonia.
[0093] In a preferred embodiment, in the method for preparing the first type of polymerizable monomer, the sodium hydroxide and part of the water are used in the form of a 32% sodium hydroxide aqueous solution; the ammonia can be used in the form of a 25% ammonia aqueous solution with part of the water.
[0094] In a preferred embodiment, the molar ratio Z of the alkaline substance to the acrylic monomer is (0.2-0.8):1 or (0.8-4):1, for example 0.4:1, 0.8:1, 1.1:1, 1.2:1, 1.3:1, 2.5:1, 3:1 or 3.4:1.
[0095] In a preferred embodiment, the molar ratio Z of the alkaline substance to the acrylic monomer is 0.2:1≤Z<0.8:1, and the polymerization reaction further includes the following post-treatment steps: neutralization; the alkaline substance used for neutralization can be ammonia or sodium hydroxide.
[0096] In a preferred embodiment, the acrylic polymer is weakly alkaline, for example, its pH value is 7-9, such as 7-8.5.
[0097] In a preferred embodiment, the polymerization method is selected from the following method A or method B:
[0098] Method A:
[0099] Step (1): in water, neutralizing an acrylic acid monomer with an alkaline substance to obtain the first type of polymerizable monomer; the molar ratio Z of the alkaline substance to the acrylic acid monomer is 0.2:1≤Z<0.8:1;
[0100] Step (2): in water, in the presence of an initiator and a protective colloid, subjecting the first type of polymerizable monomer, the second type of polymerizable monomer and the third type of polymerizable monomer in step (1) to a first stage polymerization reaction and a second stage polymerization reaction to obtain a polymer;
[0101] Step (3): neutralizing the polymer obtained in step (2) with an alkaline substance in water to obtain the acrylic polymer;
[0102] Method B:
[0103] In water, in the presence of an initiator, an alkaline substance and a protective colloid, the acrylic monomer, the second type of polymerizable monomer and the third type of polymerizable monomer are subjected to a first stage polymerization reaction and a second stage polymerization reaction to obtain the acrylic polymer; the molar ratio Z of the alkaline substance to the acrylic monomer is 0.8:1≤Z≤4:1.
[0104] In a preferred embodiment, in method A, the first type of polymerizable monomer, the second type of polymerizable monomer, the third type of polymerizable monomer and part of the water are used in the form of the polymerizable monomer solution.
[0105] In a preferred embodiment, in method A, in step (3), the molar ratio of the alkaline substance to the polymerizable monomer is (0.6-2):1, such as 0.7:1, 0.8:1, 1.1:1 or 1.2:1, and another example is 0.7:1 or 0.8:1.
[0106] In a preferred embodiment, in method B, the acrylic monomer, the second type of polymerizable monomer, the third type of polymerizable monomer and part of the water are used in the form of the polymerizable monomer solution.
[0107] In a preferred embodiment, the reaction system of the polymerization reaction consists of the following components: the solvent, the initiator, the acrylic monomer, the second type of polymerization monomer, the third type of polymerization monomer, the alkaline substance and the protective colloid; the protective colloid is polyvinyl alcohol, povidone, methacrylic resin or styrene acrylic resin.
[0108] In a preferred embodiment, the polymerization method comprises the following steps:
[0109] Step (1): neutralizing an acrylic acid monomer with an alkaline substance (such as ammonia or sodium hydroxide) in water to obtain the first type of polymerizable monomer; the molar ratio Z of the alkaline substance to the acrylic acid monomer is 0.2:1≤Z<0.8:1 (such as 0.4:1);
[0110] Step (2): in water, in the presence of ammonium persulfate and polyvinyl alcohol, subjecting the first type of polymerizable monomer, the second type of polymerizable monomer and the third type of polymerizable monomer in step (1) to a first stage polymerization reaction and a second stage polymerization reaction to obtain a polymer solution;
[0111] Step (3): neutralizing the polymer solution obtained in step (2) with an alkaline substance (such as ammonia or sodium hydroxide) in water to obtain the acrylic polymer;
[0112] In the polymerization reaction, the mass ratio of the water to the polymerization monomer is (2-5): 1;
[0113] The mass ratio of the ammonium persulfate to the polymerization monomer is (0.01-0.05):1;
[0114] The mass ratio of the polyvinyl alcohol to the polymerization monomer (0.1-1): 1;
[0115] In the step (3), the molar ratio of the alkaline substance to the polymerization monomer is (0.6-2):1;
[0116] Taking the molar percentage of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer as 100%, the definitions and molar percentages of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer meet any of the following schemes:
[0117] Scheme 1: 83% acrylic monomer, 5% methyl methacrylate and 12% third polymerizable monomer;
[0118] The acrylic monomer is composed of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 1.8:1; the third type of polymerizable monomer is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C and the weight average molecular weight is 150,000 g / mol;
[0119] Solution 2: 70% acrylic monomer, 20% ethyl acrylate and 10% hydroxypropyl methacrylate; the acrylic monomer consists of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 65°C and the weight average molecular weight is 270,000 g / mol;
[0120] Scheme 3: 60% acrylic monomer, 36% second polymerizable monomer and 4% hydroxyethyl acrylate;
[0121] The acrylic monomer consists of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 0.25:1; the second type of polymerizable monomer consists of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is 2:1; preferably, the glass transition temperature of the acrylic polymer is 81°C and the weight average molecular weight is 440,000 g / mol.
[0122] In a preferred embodiment, the polymerization method comprises the following steps:
[0123] In water, in the presence of ammonium persulfate, an alkaline substance (e.g., sodium hydroxide) and an acrylic resin (e.g., Hanwha soluryl-90 or BASF Joncryl 678 resin), the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer are subjected to a first stage polymerization reaction and a second stage polymerization reaction to obtain the acrylic polymer; the molar ratio Z of the alkaline substance to the acrylic monomer is 0.8:1≤Z≤4:1 (e.g., 0.8:1, 3:1 or 3.4:1);
[0124] In the polymerization reaction, the mass ratio of the water to the polymerization monomer is (2-5): 1;
[0125] The mass ratio of the ammonium persulfate to the polymerization monomer is (0.01-0.05):1;
[0126] The mass ratio of the acrylic resin to the polymerizable monomer (0.1-1): 1;
[0127] Taking the molar percentage of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer as 100%, the definitions and molar percentages of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer meet any of the following schemes:
[0128] Solution 1: 8% methacrylic acid, 81% methyl methacrylate and 11% hydroxyethyl acrylate; preferably, the acrylic polymer has a glass transition temperature of 120° C. and a weight average molecular weight of 620,000 g / mol;
[0129] Solution 2: 9% methacrylic acid, 78% methyl methacrylate and 13% hydroxymethyl acrylamide; preferably, the acrylic polymer has a glass transition temperature of 143° C. and a weight average molecular weight of 740,000 g / mol.
[0130] In a preferred embodiment, after the polymerization reaction is completed, the following post-treatment step is further included: filtration.
[0131] In a preferred embodiment, the acrylic polymer is the acrylic polymer as described in the first subject.
[0132] The present invention provides a method for preparing an acrylic polymer, which comprises the following steps:
[0133] In a solvent, in the presence of an initiator, the polymerization monomers of the acrylic polymer as described above are polymerized to obtain an acrylic polymer; preferably, the conditions and operation of the polymerization reaction are as described in any of the above items.
[0134] The present invention provides a composition for lithium batteries, wherein the composition comprises the acrylic polymer as described above or an aqueous solution of the acrylic polymer.
[0135] In a preferred embodiment, the acrylic polymer aqueous solution is prepared by the following method, which includes the following steps: in a solvent, in the presence of an initiator, polymerizing the polymerization monomers of the acrylic polymer as described above, and the mixed solution obtained after the polymerization reaction is the acrylic polymer aqueous solution. The conditions and operations of the method are as described above.
[0136] In a preferred embodiment, the composition does not contain polyvinylidene fluoride.
[0137] In a preferred embodiment, the composition further comprises water. Preferably, the solid content of the composition is 1%-50%, for example 3%-25%; for example 3%, 24.10%, 24.20%, 25.10%, 25.90% or 27.80%.
[0138] In a preferred embodiment, the water is the first component water or is composed of the first component water and the second component water, and the acrylic polymer and the second component water are used in the form of an acrylic polymer aqueous solution; preferably, the solid content of the acrylic polymer aqueous solution is 20%-30%, for example 24%-28%, for example 24.10%, 24.20%, 25.10%, 25.90% or 27.80%.
[0139] In a preferred embodiment, the composition comprises the acrylic polymer as described above, a first component of water and a second component of water; or the composition comprises an aqueous solution of the acrylic polymer as described above and a first component of water.
[0140] In a preferred embodiment, the composition further comprises ceramic powder.
[0141] In a preferred embodiment, the ceramic powder is selected from one or more of aluminum oxide, boehmite, silicon oxide, titanium oxide, calcium carbonate, barium sulfate and magnesium oxide, such as aluminum oxide.
[0142] In a preferred embodiment, the mass ratio of the ceramic powder to the acrylic polymer is (15-25):1, such as 18:1, 19:1, 20:1 or 21:1; for example 20:1.
[0143] In a preferred embodiment, the composition includes a first component of water, a second component of water, an acrylic polymer as described above, and a ceramic powder, or the composition includes a first component of water, an aqueous solution of an acrylic polymer, and ceramic powder; preferably, the acrylic polymer and the second component of water are used in the form of an aqueous solution of the acrylic polymer; preferably, the solid content of the composition is 10%-90%, for example 30%-50%, for example 39% or 41%; the mass ratio of the ceramic powder to the acrylic polymer may be (15-25):1; for example 18:1, 19:1, 20:1 or 21:1; for example 20:1.
[0144] In a preferred embodiment, the pH value of the composition is 7-9, such as 7-8.5.
[0145] In a preferred embodiment, the composition consists of a first component of water, a second component of water, an acrylic polymer as described above, and ceramic powder, or consists of a first component of water, an aqueous solution of an acrylic polymer, and ceramic powder; for example, the solid content of the composition is 41% or 39%; the mass ratio of the ceramic powder to the acrylic polymer is 20:1.
[0146] In a preferred embodiment, the composition comprises the following components in parts by mass: 30-60 parts of ceramic powder, 6-12 parts of acrylic polymer aqueous solution and 40-90 parts of the first component water.
[0147] In a preferred embodiment, the mass fraction of the ceramic powder is 35 parts to 55 parts, for example, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts.
[0148] In a preferred embodiment, the weight percentage of the aqueous solution of acrylic polymer is 7 parts to 11 parts, for example, 7 parts, 8 parts, 9 parts, 10 parts or 11 parts.
[0149] In a preferred embodiment, the mass fraction of the first component water is 50 parts to 85 parts, such as 52.5 parts, 60 parts, 67 parts, 75 parts or 83 parts.
[0150] In a preferred embodiment, the mass ratio of the ceramic powder to the acrylic polymer aqueous solution is (3.2-7.8):1, for example, 5:1.
[0151] In a preferred embodiment, the composition is composed of the following components in parts by mass: 30-60 parts of ceramic powder, 6-12 parts of acrylic polymer aqueous solution and 40-90 parts of the first component water, and the solid content of the composition A is 20%-30%.
[0152] In a preferred embodiment, the composition is any of the following:
[0153] Scheme 1: The composition is composed of the following components in parts by mass: 35 parts of ceramic powder, 7 parts of acrylic polymer aqueous solution and 52.5 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 24.10%;
[0154] Scheme 2: The composition is composed of the following components in parts by mass: 45 parts of ceramic powder, 9 parts of acrylic polymer aqueous solution and 67 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 25.9%;
[0155] Scheme 3: The composition is composed of the following components in parts by mass: 55 parts of ceramic powder, 11 parts of acrylic polymer aqueous solution and 83 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 24.2%;
[0156] Scheme 4: The composition is composed of the following components in parts by mass: 40 parts of ceramic powder, 8 parts of acrylic polymer aqueous solution and 60 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 27.8%;
[0157] Solution 5: The composition consists of the following components in parts by mass: 50 parts of ceramic powder, 10 parts of an acrylic polymer aqueous solution and 75 parts of a first component of water, wherein the acrylic polymer aqueous solution has a solid content of 25.1%.
[0158] In a preferred embodiment, the composition comprises the acrylic polymer and the ceramic powder; the mass ratio of the ceramic powder to the acrylic polymer and the definition of the ceramic powder are as described in any of the preceding items.
[0159] In a preferred embodiment, the composition consists of the following components: the acrylic polymer and ceramic powder as described above.
[0160] In a preferred embodiment, the composition is prepared by the following method, which includes the following steps: mixing the following components and then drying to obtain the composition; the components include a first component of water, a second component of water, an acrylic polymer as described above, and a ceramic powder, or the components include a first component of water, an aqueous solution of an acrylic polymer, and ceramic powder; the definitions of the water, acrylic polymer, aqueous solution of acrylic polymer, and ceramic powder are as described in any of the previous items.
[0161] In a preferred embodiment, the composition is in the form of a film.
[0162] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0163] The reagents and raw materials used in the present invention are commercially available.
[0164] The positive progressive effect of the present invention is that the present invention provides an acrylic polymer for a high-temperature resistant lithium battery, a composition containing the same and a preparation method. The acrylic polymer provided by the present invention can be used without adding other functional additives, and after mixing with ceramic powder, it can be used as a ceramic slurry for lithium batteries to coat the surface of the base film, and has good peel strength and heat resistance, reduces the use of polymer materials in the ceramic slurry, and avoids the adverse effects of high molecular weight materials on electrical properties caused by free electrolytes. DETAILED DESCRIPTION
[0165] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0166] The parts in the following examples are all parts by mass.
[0167] The percentages of the various components in the following examples refer to mass percentages.
[0168] In the following examples, the pH of the obtained solution-type adhesive is weakly alkaline, for example, pH 7-8.5.
[0169] The coating process in the embodiment uses a coating machine model of GTB 400B, which is a micro-gravure coating method. The coating thickness is 3 μm, the thickness of the polyolefin separator is 9 μm, and the coating is dried at a temperature of 50°C.
[0170] Example 1
[0171] Add 35 parts of ceramic powder aluminum oxide, 52.5 parts of deionized water, and 7 parts of solution-type binder 1 to a beaker, disperse them evenly with a disperser (to ensure that no sedimentation occurs during use), and apply them to the polyolefin separator. The solid content of solution-type binder 1 is 5% (the mass percentage of the polymer in the binder to the ceramic powder).
[0172] The glass transition temperature of the solution-type binder 1 is 112° C., and the weight average molecular weight is 150,000 g / mol.
[0173] The raw materials of solution-type adhesive 1 are hydrophilic monomers 5.2% methacrylic acid and 9.6% acrylic acid, totaling 14.8%, lipophilic monomers 1.2% methyl methacrylate, hydroxyl monomers 1.98% hydroxymethyl acrylamide and 0.95% hydroxyethyl methacrylate, totaling 2.93%, protective colloid 2.4% polyvinyl alcohol, initiator 0.52% ammonium persulfate, neutralizing agent 14.95% 25% ammonia solution, and deionized water 63.2%.
[0174] The preparation method of the solution type binder 1 is as follows:
[0175] In a 500mL four-necked round-bottom flask, add 150g of deionized water and 12.00g of PVA (polyvinyl alcohol, degree of alcoholysis 88%) in sequence, install a condenser, a thermometer, and a feeding tube, start stirring, and heat to 80°C.
[0176] Prepare a monomer solution, place a beaker in an ice water bath, add 26g methacrylic acid, 48g acrylic acid, 6g methyl methacrylate, 4.76g hydroxyethyl methacrylate, 19.83g 50% by mass hydroxymethyl acrylamide deionized water solution, 80g deionized water, 25.3g 25% ammonia solution in sequence, and stir for 10 minutes.
[0177] To prepare the initiator solution, add 40 g of deionized water and 2.62 g of ammonium persulfate into a beaker until completely dissolved.
[0178] 21 g of monomer solution and 4.2 g of initiator solution were added to a four-necked flask, and after reacting for 30 min, the remaining monomer solution and initiator solution were added dropwise for 120 min. After the addition was completed, the mixture was kept warm for 60 min, cooled to below 50° C., 49.43 g of 25% ammonia solution and 36.06 g of deionized water were added, stirred for 10 min, and the material was filtered to obtain a solution-type binder 1. The solid content was measured to be 24.10%.
[0179] Example 2
[0180] Add 45 parts of ceramic powder (alumina), 67 parts of deionized water, and 9 parts of solution-type binder 2 into a beaker, disperse them evenly with a disperser, and apply them on the polyolefin separator. The solid content of solution-type binder 2 is 5% (the mass percentage of polymer in the binder to the ceramic powder).
[0181] The glass transition temperature of the solution-type binder 2 is 65° C., and the weight average molecular weight is 270,000 g / mol.
[0182] The raw materials of solution-type adhesive 2 are hydrophilic monomers methacrylic acid 4.0% and acrylic acid 7.6% totaling 11.6%, lipophilic monomer ethyl acrylate 4.4%, hydroxyl monomer hydroxypropyl methacrylate 2.92%, protective colloid polyvinyl alcohol 5.0%, initiator ammonium persulfate 0.28%, neutralizing agent 25% ammonia solution 11.6%, and deionized water 64.20%.
[0183] The preparation method is as follows:
[0184] In a 500mL four-necked round-bottom flask, add 150g of deionized water and 25.00g of PVA in sequence, install a condenser, a thermometer, and a feeding tube, start stirring, and heat to 80°C.
[0185] Prepare a monomer solution, place a beaker in an ice water bath, add 20 g methacrylic acid, 38 g acrylic acid, 22 g ethyl acrylate, 14.59 g hydroxypropyl methacrylate, 80 g deionized water, and 17.3 g 25% ammonia solution in sequence, and stir for 10 minutes.
[0186] To prepare the initiator solution, add 40 g of deionized water and 1.4 g of ammonium persulfate into a beaker until completely dissolved.
[0187] 19.2 g of monomer solution and 4.2 g of initiator solution were added to a four-necked flask. After reacting for 30 min, the remaining monomer solution and initiator solution were added dropwise for 120 min. After the addition was completed, the mixture was kept warm for 60 min, cooled to below 50° C., 40.7 g of 25% ammonia solution and 51.01 g of deionized water were added, stirred for 10 min, and the material was filtered to obtain a solution-type binder 2. The solid content was measured to be 25.90%.
[0188] Example 3
[0189] Add 55 parts of ceramic powder (alumina), 83 parts of deionized water, and 11 parts of solution type binder 3 into a beaker, disperse them evenly with a disperser, and apply them on the polyolefin separator. The solid content of solution type binder 3 is 5% (the mass percentage of polymer in the binder to ceramic powder).
[0190] The glass transition temperature of the solution-type binder 3 is 81° C., and the weight average molecular weight is 440,000 g / mol.
[0191] The raw materials of solution-type adhesive 3 are hydrophilic monomers of methacrylic acid 6.41% and acrylic acid 1.6% totaling 8.01%, lipophilic monomers of ethyl acrylate 2.0% and methyl methacrylate 4.4% totaling 6.4%, hydroxyl monomer of hydroxyethyl acrylate 1.06%, protective colloid of polyvinyl alcohol 8.01%, initiator of ammonium persulfate 0.20%, neutralizing agent of 32% sodium hydroxide solution 10.41%, and deionized water 65.91%.
[0192] The preparation method is as follows:
[0193] In a 500mL four-necked round-bottom flask, add 230g of deionized water and 40.00g of PVA in sequence, install a condenser, a thermometer, and a feeding tube, start stirring, and heat to 80°C.
[0194] Prepare a monomer solution by sequentially adding 32 g of methacrylic acid, 8 g of acrylic acid, 10 g of ethyl acrylate, 5.3 g of hydroxyethyl acrylate, 22 g of methyl methacrylate, and 22 g of 32% sodium hydroxide into a beaker and stirring for 10 min.
[0195] Prepare the initiator solution by adding 40 g of deionized water and 1.0 g of ammonium persulfate into a beaker until completely dissolved.
[0196] 7.7 g of monomer solution and 4.1 g of initiator solution were added to a four-necked flask. After reacting for 30 min, the remaining monomer solution and initiator solution were added dropwise for 120 min. After the addition was completed, the mixture was kept warm for 60 min, cooled to below 50° C., 52.00 g of 32% sodium hydroxide solution and 59.3 g of deionized water were added, stirred for 10 min, and the material was filtered to obtain a solution-type binder 3. The solid content was measured to be 24.20%.
[0197] Example 4
[0198] Add 40 parts of ceramic powder (alumina), 60 parts of deionized water, and 8 parts of solution-type binder 4 into a beaker, disperse them evenly with a disperser, and apply them on the polyolefin separator. The solid content of solution-type binder 4 is 5% (the mass percentage of polymer in the binder to the ceramic powder).
[0199] The glass transition temperature of the solution-type binder 3 is 120° C., and the weight average molecular weight is 620,000 g / mol.
[0200] The raw materials of solution-type adhesive 4 are hydrophilic monomer methacrylic acid 1.2%, lipophilic monomer methyl methacrylate 14.0%, hydroxyl monomer hydroxyethyl acrylate 2.0%, protective colloid Hanwha soluryl-90 resin 9.6%, initiator ammonium persulfate 0.20%, neutralizing agent 32% sodium hydroxide solution 6.0%, and deionized water 67.0%.
[0201] The preparation method is as follows:
[0202] In a 500mL four-necked round-bottom flask, add 230g of deionized water, 48.00g of Hanwha soluryl-90 resin (soluryl-90 resin parameters are: molecular weight 9500g / mol, acid value 218mgKOH / g), and 30g of 32% sodium hydroxide in sequence, install a condenser, a thermometer, and a feeding tube, start stirring and heat to 80°C, and keep warm for 120min until the resin is completely dissolved.
[0203] Prepare a monomer solution by adding 6 g of methacrylic acid, 70 g of methyl methacrylate, and 10 g of hydroxyethyl acrylate into a beaker in sequence and stirring for 10 minutes.
[0204] Prepare the initiator solution by adding 40 g of deionized water and 1.0 g of ammonium persulfate into a beaker until completely dissolved.
[0205] 8.6 g of monomer solution and 4.1 g of initiator solution were added to a four-necked flask. After reacting for 30 min, the remaining monomer solution and initiator solution were added dropwise for 120 min. After the addition was completed, the mixture was kept warm for 60 min, cooled to below 50° C., 65 g of deionized water was added, stirred for 10 min, and the material was filtered to obtain a solution-type binder 3. The solid content was measured to be 27.80%.
[0206] Example 5
[0207] Add 50 parts of ceramic powder (alumina), 75 parts of deionized water, and 10 parts of solution-type binder 5 into a beaker, disperse them evenly with a disperser, and apply them on the polyolefin separator. The solid content of solution-type binder 5 is 5% (the mass percentage of polymer in the binder to ceramic powder).
[0208] The glass transition temperature of the solution-type binder 5 is 143° C., and the weight average molecular weight is 740,000 g / mol.
[0209] The raw materials of solution-type adhesive 5 are hydrophilic monomer methacrylic acid 1.24%, lipophilic monomer methyl methacrylate 12.44%, hydroxyl monomer hydroxymethyl acrylamide 2.07%, protective colloid BASF Joncryl 678 resin 7.05%, initiator ammonium persulfate 0.31%, neutralizing agent 32% sodium hydroxide solution 5.39%, and deionized water 71.5%.
[0210] The preparation method is as follows:
[0211] In a 500mL four-necked round-bottom flask, add 230g of deionized water, 34.00g of BASF Joncryl 678 resin (molecular weight 8600g / mol, acid value 215mgKOH / g), and 26g of 32% sodium hydroxide in sequence, install a condenser, a thermometer, and a feeding tube, start stirring, heat to 80°C, and keep warm for 120min until the resin is completely dissolved.
[0212] To prepare a monomer solution, 6 g of methacrylic acid, 60 g of methyl methacrylate, and 20 g of a 50% by mass solution of hydroxymethyl acrylamide in deionized water were added to a beaker in sequence, and stirred for 10 minutes.
[0213] Prepare the initiator solution by adding 40 g of deionized water and 1.5 g of ammonium persulfate into a beaker until completely dissolved.
[0214] 8.6 g of monomer solution and 4.1 g of initiator solution were added to a four-necked flask. After reacting for 30 min, the remaining monomer solution and initiator solution were added dropwise for 120 min. After the addition was completed, the mixture was kept warm for 60 min, cooled to below 50° C., 65 g of deionized water was added, stirred for 10 min, and the material was filtered to obtain a solution-type binder 3. The solid content was measured to be 25.10%.
[0215] Comparative Example 1
[0216] The comparative binder is a styrene-butadiene latex binder. 1.18 g CMC thickener and 118.82 g deionized water are added to a beaker, stirred until the CMC is completely dissolved, and then 80.0 g aluminum oxide and 0.2 g sodium polyacrylate dispersant are added to the beaker, and dispersed evenly with a disperser or a ball mill. After uniform dispersion, 0.2 g of organosilicon wetting agent and 10 g of styrene-butadiene latex binder are added to the beaker, and the dispersion is continued to be uniform to obtain a ceramic slurry, which is applied on the surface of the polyolefin diaphragm.
[0217] Comparative Example 2
[0218] The adhesive for comparison is an acrylic emulsion adhesive. The preparation method thereof is as follows:
[0219] Prepare the pre-emulsion: add 13.17 g of methyl methacrylate, 27.22 g of isooctyl acrylate, 1.17 g of methacrylic acid, 0.88 g of emulsifier CO436, and 28.53 g of deionized water into a beaker and stir for 30 minutes to emulsify.
[0220] Prepare the initiator: add 9.51 g of deionized water, 0.19 g of ammonium persulfate, and 0.19 g of sodium bicarbonate into a beaker and stir for 10 min until completely dissolved.
[0221] Emulsion polymerization: Add 10.56g of deionized water and 0.22g of emulsifier CO436 to a 500mL flask, install a condenser and a thermometer, start stirring, and heat to 80°C; then add 0.04g of ammonium persulfate and 3.95g of 6% pre-emulsion. Wait for 5-10 minutes, blue fluorescence appears, and start dripping the initiator and the remaining pre-emulsion. Add for 120 minutes, and control the temperature at 78-82°C. After the addition is completed, keep warm for 60 minutes and cool down to below 50°C. Add 1.5g of 25% ammonia solution and 1.5g of deionized water, stir for 30 minutes, and filter the material to obtain an acrylic emulsion adhesive. The solid content was measured to be 41.5%
[0222] Add 1.18g CMC thickener and 118.82g deionized water to a beaker, stir until the CMC is completely dissolved, then add 80.0g alumina and 0.2g sodium polyacrylate dispersant to the beaker, and disperse evenly with a disperser or ball mill. After uniform dispersion, add 0.2g of silicone wetting agent and 9.64g of acrylate emulsion binder to the beaker, continue to disperse evenly to obtain ceramic slurry, and apply it on the surface of the polyolefin diaphragm.
[0223] Effect embodiment 1:
[0224] The coated heat-resistant diaphragm was obtained by coating on a machine, and then a 200*30mm sample was taken, and a 20mm 3M tape was flatly attached along the MD direction. The peel strength was tested using a tensile testing machine with a test speed of 50mm / min, a range of 50mm, and a test width of 20mm.
[0225] Increased air permeability: Take a sample of 100*100mm and use an air permeability meter to test the time required for 100cc of air to pass through a 6.45cm2 membrane. Use the same method to test the air permeability of the substrate. The difference between the two values is the increased air permeability.
[0226] Heat resistance: Take a sample of 100*100mm, place 1 A4 paper on the top and bottom, put it in a 150℃ blast-type thermostatic box for 1 hour, and measure the length and width.
[0227] Moisture value: Take a sample of the newly coated diaphragm and place it in a drying bottle. Use the Coulometric method to test the moisture value of the diaphragm.
[0228] The test results of the ceramic slurry coated diaphragms obtained in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.
[0229] Table 1 Test data
[0230]
[0231]
[0232] According to the above test data, the results show that the air permeability and moisture content of the diaphragms coated in Examples 1-5 are similar to those of Comparative Examples 1 and 2, and the peel strength and 150° C. heat resistance are much better than those of Comparative Examples 1 and 2.
[0233] Compared with Comparative Examples 1 and 2, the slurry obtained in the present invention does not require the addition of various additives, such as dispersants, wetting agents and thickeners, which simplifies the preparation process of the ceramic slurry and reduces the overall cost of the coated diaphragm. At the same time, the coated diaphragm has higher peel strength and heat resistance.
Claims
1. An acrylic polymer, characterized in that: The acrylic polymer is composed of a first type of structural unit, a second type of structural unit and a third type of structural unit; The first type of structural unit is selected from One or more of; The second structural unit is selected from One or more of; The third type of structural unit is selected from One or more of; R 1 , R 2 , R 3 and R 4 are independently -OH, -OLi, -ONa, -OK, -ONH4 or And not OH at the same time; Taking the total molar number of the first structural unit, the second structural unit and the third structural unit as 100%, in the acrylic polymer, the molar percentage of the first structural unit is 5%-85%, the molar percentage of the second structural unit is 4%-85%; and the molar percentage of the third structural unit is 2%-15%; The weight average molecular weight of the acrylic polymer is 100,000-800,000 g / mol; The acrylic polymer is a random copolymer.
2. The acrylic polymer according to claim 1, characterized in that It meets one or more of the following conditions: (1)R 1 , R 2 , R 3 and R 4 are independently -OH, ONa or -ONH4; (2) The molar percentage of the first type of structural unit is 8% to 83%, for example 8%, 9%, 60%, 70% or 83%; (3) The first type of structural unit is Composition, R 1 is -ONa or -ONH4; R 2 is -OH, -ONa or -ONH4; Preferably, the first type of structural unit consists of Composition, R 1 and R 2 At the same time, it is -ONa or -ONH4; The molar ratio is (0.1-3):1, such as 0.25:1, 2.3:1 or 2.5:1; for example, the first type of structural unit is composed of composition; Alternatively, the first type of structural unit is R 2 is -OH, -ONa or -ONH4, for example, the first type of structural unit is composition, The molar ratio is 1:4; (4) the molar percentage of the second structural unit is 5%-81%, for example 5%, 20%, 36%, 78% or 81%; (5) The second type of structural unit is Preferably, the second structural unit is composed of Composition, the The molar ratio is (1-3):1, for example 2:1; (6) The molar percentage of the third structural unit is 4% to 13%, for example 4%, 10%, 11%, 12% or 13%; (7) The third type of structural unit is or by Preferably, the third type of structural unit consists of Composition, the The molar ratio is (1-3):1, for example 2.5:1; (8) The weight average molecular weight of the acrylic polymer is 150,000-740,000 g / mol, for example, 150,000 g / mol, 270,000 g / mol, 440,000 g / mol, 620,000 g / mol or 740,000 g / mol; (9) The glass transition temperature of the acrylic polymer is 60-150°C, for example, 65°C, 81°C, 112°C, 120°C or 143°C; (10) the pH value of the acrylic polymer is 7-9, for example 7-8.5; and (11) In the first type of structural unit, the substituent R 1 , R 2 , R 3 and R 4 The total molar number is calculated as 100%, R 1 , R 2 , R 3 and R 4 The molar percentage of -OH in is 0-20%; for example 0 or 20%; Preferably, the structural unit is selected from any of the following schemes: Scheme 1: The structural unit is composed of the following molar percentages of structural units: 83% of the first structural unit, 5% of the second structural unit and 12% of the third structural unit; The first type of structural unit is composed of Composition, the The molar ratio is 2.3:1; the second structural unit is The third type of structural unit is composed of Composition, the The molar ratio is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C and the weight average molecular weight is 150,000 g / mol; Scheme 2: The structural unit is composed of the following molar percentages of structural units: 70% of the first structural unit, 20% of the second structural unit and 10% of the third structural unit; The first type of structural unit is composed of Composition, the The molar ratio is 2.5:1; the second structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 65°C and a weight average molecular weight of 270,000 g / mol; Scheme 3: The structural unit is composed of the following molar percentages of structural units: 60% of the first structural unit, 36% of the second structural unit and 4% of the third structural unit; The first type of structural unit is composed of Composition, the The molar ratio is 0.25:1; the second structural unit is composed of Composition, the The molar ratio is 2:1; the third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 81°C and a weight average molecular weight of 440,000 g / mol; Scheme 4: The structural unit is composed of the following molar percentages of structural units: 8% of the first structural unit, 81% of the second structural unit and 11% of the third structural unit; The first type of structural unit is The molar ratio is 1:4; the second structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 120°C and a weight average molecular weight of 620,000 g / mol; Scheme 5: The structural unit is composed of the following mole percentages of structural units: 9% of the first structural unit, 78% of the second structural unit and 13% of the third structural unit; The first type of structural unit is The second type of structural unit is The third type of structural unit is Preferably, the acrylic polymer has a glass transition temperature of 143° C. and a weight average molecular weight of 740,000 g / mol.
3. An acrylic polymer, characterized in that The acrylic polymer is prepared by the following polymerization method, which comprises the following steps: in a solvent, in the presence of an initiator, polymerizing a polymerizable monomer to obtain the acrylic polymer; The polymerizable monomers include 5%-85% of a first polymerizable monomer, 4%-85% of a second polymerizable monomer, and 2%-15% of a third polymerizable monomer, wherein the percentages are respectively the molar percentages of the molar number of the first polymerizable monomer, the second polymerizable monomer, or the third polymerizable monomer to the total molar number of each polymerizable monomer of the acrylic polymer, The first type of polymerizable monomer is selected from One or more of R 1 , R 2 , R 3 and R 4 are independently -OH, -OLi, -ONa, -OK, -ONH4 or And not OH at the same time; The second type of polymerizable monomer is selected from one or more of methyl methacrylate, ethyl acrylate, butyl acrylate, ethyl methacrylate, cyclohexyl methacrylate and acrylonitrile; The third type of polymerizable monomer is selected from one or more of hydroxymethyl acrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate; The weight average molecular weight of the acrylic polymer is 100,000-800,000 g / mol; The acrylic polymer is a random copolymer.
4. The acrylic polymer according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In the first type of polymerizable monomer, the substituent R 1 , R 2 , R 3 and R 4 The total molar number is calculated as 100%, R 1 , R 2 , R 3 and R 4 The molar percentage of -OH in the 1 , R 2 , R 3 and R 4 When the molar percentage of -OH in the polymerization reaction is greater than 80%, the polymerization reaction further comprises the following post-treatment steps: neutralization; the alkaline substance used for neutralization may be ammonia or sodium hydroxide; preferably, R 1 , R 2 , R 3 and R 4 are independently -OH, ONa or -ONH4; (2) The first type of polymerizable monomer is R 1 is -ONa or -ONH4; R 2 is -OH, -ONa or -ONH4; Preferably, the first type of polymerizable monomer is The composition of R 1 and R 2 At the same time, it is -ONa or -ONH4; The molar ratio is (0.1-3):1, for example, 0.25:1, 2.3:1 or 2.5:1; for example, the first structural unit is composed of ammonium acrylate and ammonium methacrylate or sodium acrylate and sodium methacrylate; Alternatively, the first type of polymerizable monomer is R 2 is -OH, -ONa or -ONH4, for example, the first structural unit is sodium methacrylate or is composed of methacrylic acid and sodium methacrylate, and the molar ratio of methacrylic acid to sodium methacrylate is 1:4; (3) the molar percentage of the first type of polymerizable monomer is 8% to 83%, for example 8%, 9%, 60%, 70% or 83%; (4) The second type of polymerizable monomer is methyl methacrylate, ethyl acrylate, or is composed of methyl methacrylate and ethyl acrylate; preferably, the second type of polymerizable monomer is composed of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is (1-3):1, for example, 2:1; (5) the mole percentage of the second type of polymerizable monomer is 5% to 81%, for example, 5%, 20%, 36%, 78% or 81%; (6) The third type of polymerizable monomer is hydroxypropyl methacrylate, hydroxyethyl acrylate, hydroxymethyl acrylamide, or hydroxymethyl acrylamide and hydroxyethyl methacrylate; preferably, the third type of polymerizable monomer is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is (1-3):1, for example, 2.5:1; (7) The molar percentage of the third type of polymerizable monomer is 5% to 25%, for example, 6.86%, 11.63%, 13.16%, 15.42% or 15.5%; (8) The weight average molecular weight of the acrylic polymer is 150,000-740,000 g / mol, for example, 150,000 g / mol, 270,000 g / mol, 440,000 g / mol, 620,000 g / mol or 740,000 g / mol; (9) The glass transition temperature of the acrylic polymer is 60-150°C, for example, 65°C, 81°C, 112°C, 120°C or 143°C; (10) The polymerizable monomer and part of the solvent are used in the form of a polymerizable monomer solution, wherein the mass percentage of the polymerizable monomer in the polymerizable monomer solution may be 40%-90%, for example, 46%, 50%, 84% or 88%; (11) The solvent is water, such as deionized water; (12) In the polymerization reaction, the mass ratio of the solvent to the polymerization monomer is (2-5): 1, for example, 3:1, 3.2:1, 3.4:1, 3.7:1 or 3.9:1; (13) The initiator is selected from one or more of ammonium persulfate, sodium persulfate and a redox system consisting of vitamin C and sodium persulfate; for example, ammonium persulfate; (14) The mass ratio of the initiator to the polymerization monomer is (0.01-0.05):1, for example, 0.012:1, 0.013:1, 0.015:1, 0.02:1 or 0.028:1; (15) The initiator and part of the solvent are used in the form of an initiator solution, and the mass percentage of the initiator in the initiator solution can be 1%-10%, for example, 2%, 3%, 4% or 6%. (16) The polymerization reaction system further comprises a protective colloid, wherein the protective colloid is selected from one or more of acrylic resin, polyvinyl alcohol and povidone, such as acrylic resin or polyvinyl alcohol; (17) The mass ratio of the protective colloid to the polymerized monomer is (0.1-1):1, for example, 0.13:1, 0.26:1, 0.45:1, 0.52:1 or 0.56:1; (18) The pH value of the acrylic polymer is 7-9, for example 7-8.5; (19) The polymerization reaction is divided into a first stage polymerization reaction and a second stage polymerization reaction; preferably, the mass of the polymerization monomer added in the first stage polymerization reaction accounts for 8%-12% of the total mass of the polymerization monomer, for example, 9%-11%, and for example, 10%; the mass of the initiator added in the first stage polymerization reaction accounts for 8%-12% of the total mass of the initiator, for example, 9%-11%, and for example, 10%; (20) After the polymerization reaction is completed, the following post-treatment steps are further included: filtration; and (21) The acrylic polymer is the acrylic polymer as claimed in claim 1 or 2; Preferably, the acrylic polymer satisfies one or more of the following conditions: (1) The polymerized monomers of the acrylic polymer are composed of the following polymerized monomers in molar percentage: 5%-85% of the first polymerized monomer, 4%-85% of the second polymerized monomer and 2%-15% of the third polymerized monomer; for example, the polymerized monomers are selected from any of the following schemes: Scheme 1: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 83% of the first type of polymerizable monomers, 5% of the second type of polymerizable monomers, and 12% of the third type of polymerizable monomers; The first type of polymerizable monomers is composed of ammonium acrylate and ammonium methacrylate, and the molar ratio of ammonium acrylate to ammonium methacrylate is 2.3:1; the second type of polymerizable monomers is methyl methacrylate; the third type of polymerizable monomers is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C, and the weight average molecular weight is 150,000 g / mol; Scheme 2: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 70% of the first type of polymerizable monomers, 20% of the second type of polymerizable monomers and 10% of the third type of polymerizable monomers; The first type of polymerizable monomer is composed of ammonium acrylate and ammonium methacrylate, and the molar ratio of ammonium acrylate to ammonium methacrylate is 2.5:1; the second type of polymerizable monomer is ethyl acrylate; the third type of polymerizable monomer is hydroxypropyl methacrylate; preferably, the glass transition temperature of the acrylic polymer is 65°C, and the weight average molecular weight is 270,000 g / mol; Scheme 3: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 60% of the first type of polymerizable monomers, 36% of the second type of polymerizable monomers, and 4% of the third type of polymerizable monomers; The first type of polymerizable monomers is composed of sodium acrylate and sodium methacrylate, and the molar ratio of sodium acrylate to sodium methacrylate is 0.25:1; the second type of polymerizable monomers is composed of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is 2:1; the third type of polymerizable monomer is hydroxyethyl acrylate; Scheme 4: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 8% of the first type of polymerizable monomers, 81% of the second type of polymerizable monomers, and 11% of the third type of polymerizable monomers; The first type of polymerizable monomer is composed of methacrylic acid and sodium methacrylate, and the molar ratio of methacrylic acid to sodium methacrylate is 1:4; the second type of polymerizable monomer is methyl methacrylate; and the third type of polymerizable monomer is hydroxyethyl acrylate; Scheme 5: The polymerizable monomers are composed of the following mole percentages of polymerizable monomers: 9% of the first polymerizable monomer, 78% of the second polymerizable monomer, and 13% of the third polymerizable monomer; The first type of polymerizable monomer is sodium methacrylate; the second type of polymerizable monomer is methyl methacrylate; the third type of polymerizable monomer is hydroxymethyl acrylamide; (2) The polymerization method further includes a method for preparing the first type of polymerizable monomer, wherein the first type of polymerizable monomer is prepared by the following method, and the preparation method of the first type of polymerizable monomer includes the following steps: in water, an acrylic acid monomer is subjected to a neutralization reaction with an alkaline substance to obtain the first type of polymerizable monomer, wherein the acrylic acid monomer is selected from one or more of acrylic acid, methacrylic acid, maleic acid and fumaric acid, and the alkaline substance is selected from one or more of sodium hydroxide, ammonia, monoethanolamine and lithium hydroxide; the molar ratio Z of the alkaline substance to the acrylic acid monomer may be (0.2-5):1, for example (0.2-4):1, and for example 0.2:1≤Z<0.8:1 or 0.8:1≤Z≤4:1; (3) the alcoholysis degree of the polyvinyl alcohol is 80%-90%, for example 88%; and (4) The molecular weight of the acrylic resin is 6000-1000 g / mol, and the acid value is 200-230 mgKOH / g; preferably, the acrylic resin is methacrylic resin or styrene acrylic resin; more preferably, the molecular weight of the methacrylic resin is 9500g / mol, acid value is 218mgKOH / g or molecular weight is 7000g / mol, acid value is 218mgKOH / g; Such as Hanwha Soluryl -70 or Hanhua soluryl-90; the molecular weight of the styrene acrylic resin is 8600 g / mol and the acid value is 215 mgKOH / g, such as BASF Joncryl 678; More preferably, the acrylic polymer satisfies one or more of the following conditions: (1) The acrylic monomer is acrylic acid, methacrylic acid, or acrylic acid and methacrylic acid; the amount of the acrylic monomer is the same as the amount of the first type of polymerizable monomer; (2) The alkaline substance is sodium hydroxide or ammonia; preferably, in the method for preparing the first type of polymerizable monomer, the sodium hydroxide and part of the water are used in the form of a 32% sodium hydroxide aqueous solution; the ammonia can be used in the form of a 25% ammonia aqueous solution with part of the water; and (3) The molar ratio Z of the alkaline substance to the acrylic monomer is (0.2-0.8):1 or (0.8-4):1, for example 0.4:1, 0.8:1, 1.1:1, 1.2:1, 1.3:1, 2.5:1, 3:1 or 3.4:1; when the molar ratio Z of the alkaline substance to the acrylic monomer is 0.2:1≤Z<0.8, the polymerization reaction may further include the following post-treatment steps: neutralization; the alkaline substance used for neutralization may be ammonia or sodium hydroxide.
5. The acrylic polymer according to claim 4, characterized in that The polymerization method is selected from the following method A or method B: Method A: Step (1): in water, neutralizing an acrylic acid monomer with an alkaline substance to obtain the first type of polymerizable monomer; the molar ratio Z of the alkaline substance to the acrylic acid monomer is 0.2:1≤Z<0.8:1; Step (2): in water, in the presence of an initiator and a protective colloid, subjecting the first type of polymerizable monomer, the second type of polymerizable monomer and the third type of polymerizable monomer in step (1) to a first stage polymerization reaction and a second stage polymerization reaction to obtain a polymer solution; Step (3): neutralizing the polymer solution obtained in step (2) with an alkaline substance in water to obtain the acrylic polymer; Method B: In water, in the presence of an initiator, an alkaline substance and a protective colloid, the acrylic monomer, the second type of polymerizable monomer and the third type of polymerizable monomer are subjected to a first stage polymerization reaction and a second stage polymerization reaction to obtain the acrylic polymer; the molar ratio Z of the alkaline substance to the acrylic monomer is 0.8:1≤Z≤4:1; Preferably, the polymerization method satisfies one or more of the following conditions: (1) In method A, the first type of polymerizable monomer, the second type of polymerizable monomer, the third type of polymerizable monomer and part of the water are used in the form of the polymerizable monomer solution; (2) In method A, in step (3), the molar ratio of the alkaline substance to the polymerizable monomer is (0.6-2):1, such as 0.7:1, 0.8:1, 1.1:1 or 1.2:1, and further such as 0.7:1 or 0.8:1; (3) In method B, the acrylic monomer, the second polymerizable monomer, the third polymerizable monomer and part of the water are used in the form of the polymerizable monomer solution; (4) The reaction system of the polymerization reaction is composed of the following components: the solvent, the initiator, the acrylic monomer, the second type of polymerizable monomer, the third type of polymerizable monomer, the alkaline substance and the protective colloid; the protective colloid is polyvinyl alcohol, povidone, methacrylic resin or styrene acrylic resin; More preferably, the polymerization method is selected from the following method A or method B: Method A: The polymerization method comprises the following steps: Step (1): neutralizing an acrylic acid monomer with an alkaline substance (such as ammonia or sodium hydroxide) in water to obtain the first type of polymerizable monomer; the molar ratio Z of the alkaline substance to the acrylic acid monomer is 0.2:1≤Z<0.8:1 (such as 0.4:1); Step (2): in water, in the presence of ammonium persulfate and polyvinyl alcohol, subjecting the first type of polymerizable monomer, the second type of polymerizable monomer and the third type of polymerizable monomer in step (1) to a first stage polymerization reaction and a second stage polymerization reaction to obtain a polymer; Step (3): neutralizing the polymer obtained in step (2) with an alkaline substance (such as ammonia or sodium hydroxide) in water to obtain the acrylic polymer; In the polymerization reaction, the mass ratio of the water to the polymerization monomer is (2-5): 1; The mass ratio of the ammonium persulfate to the polymerization monomer is (0.01-0.05):1; The mass ratio of the polyvinyl alcohol to the polymerization monomer (0.1-1): 1; In the step (3), the molar ratio of the alkaline substance to the polymerization monomer is (0.6-2):1; Taking the molar percentage of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer as 100%, the definitions and molar percentages of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer meet any of the following schemes: Scheme 1: 83% acrylic monomer, 5% methyl methacrylate and 12% third polymerizable monomer; The acrylic monomer is composed of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 2.3:1; the third type of polymerizable monomer is composed of hydroxymethyl acrylamide and hydroxyethyl methacrylate, and the molar ratio of hydroxymethyl acrylamide to hydroxyethyl methacrylate is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 112°C, and the weight average molecular weight is 150,000 g / mol; Solution 2: 70% acrylic monomer, 20% ethyl acrylate and 10% hydroxypropyl methacrylate; the acrylic monomer consists of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 2.5:1; preferably, the glass transition temperature of the acrylic polymer is 65°C and the weight average molecular weight is 270,000 g / mol; Scheme 3: 60% acrylic monomer, 36% second polymerizable monomer and 4% hydroxyethyl acrylate; The acrylic monomer is composed of acrylic acid and methacrylic acid, and the molar ratio of acrylic acid to methacrylic acid is 0.25:1; the second type of polymerizable monomer is composed of methyl methacrylate and ethyl acrylate, and the molar ratio of methyl methacrylate to ethyl acrylate is 2:1; preferably, the glass transition temperature of the acrylic polymer is 81°C, and the weight average molecular weight is 440,000 g / mol; Method B: The polymerization method comprises the following steps: In water, in the presence of ammonium persulfate, an alkaline substance (e.g., sodium hydroxide) and an acrylic resin (e.g., Hanwha soluryl-90 or BASF Joncryl 678 resin), the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer are subjected to a first stage polymerization reaction and a second stage polymerization reaction to obtain the acrylic polymer; the molar ratio Z of the alkaline substance to the acrylic monomer is 0.8:1≤Z≤4:1 (e.g., 0.8:1, 3:1 or 3.4:1); In the polymerization reaction, the mass ratio of the water to the polymerization monomer is (2-5): 1; The mass ratio of the ammonium persulfate to the polymerization monomer is (0.01-0.05):1; The mass ratio of the acrylic resin to the polymerizable monomer (0.1-1): 1; Taking the molar percentage of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer as 100%, the definitions and molar percentages of the acrylic monomer, the second polymerizable monomer and the third polymerizable monomer meet any of the following schemes: Solution 1: 8% methacrylic acid, 81% methyl methacrylate and 11% hydroxyethyl acrylate; preferably, the acrylic polymer has a glass transition temperature of 120° C. and a weight average molecular weight of 620,000 g / mol; Solution 2: 9% methacrylic acid, 78% methyl methacrylate and 13% hydroxymethyl acrylamide; preferably, the acrylic polymer has a glass transition temperature of 143° C. and a weight average molecular weight of 740,000 g / mol.
6. A method for preparing an acrylic polymer, characterized in that: It includes the following steps: In a solvent, in the presence of an initiator, the polymerization monomer of the acrylic polymer as described in any one of claims 3 to 5 is polymerized to obtain an acrylic polymer; preferably, the conditions and operation of the polymerization reaction are as described in any one of claims 3 to 5.
7. A composition for lithium battery, characterized in that: The composition comprises an acrylic polymer as claimed in any one of claims 1 to 5 or an aqueous solution of the acrylic polymer as claimed in any one of claims 1 to 5; Preferably, the composition satisfies one or both of the following conditions: (1) The composition does not contain polyvinylidene fluoride; (2) The acrylic polymer aqueous solution is prepared by the following method, which comprises the following steps: in a solvent, in the presence of an initiator, subjecting the polymerizable monomers of the acrylic polymer to a polymerization reaction, wherein the mixed solution obtained after the polymerization reaction is the acrylic polymer aqueous solution, wherein the definitions of the solvent, initiator and polymerizable monomers are as described in any one of claims 3 to 5, and the conditions and operations of the method are as described in any one of claims 3 to 5.
8. The composition for lithium battery according to claim 7, characterized in that: The composition also includes water; Preferably, the composition satisfies one or more of the following conditions: (1) The pH value of the composition is 7-9, for example 7-8.5; (2) The solid content of the composition is 1%-50%, for example 3%-25%; for example 3%, 24.10%, 24.20%, 25.10%, 25.90% or 27.80%; (3) The water is first component water or is composed of first component water and second component water. Preferably, the acrylic polymer and the second component water are used in the form of an aqueous solution of the acrylic polymer. The solid content of the aqueous solution of the acrylic polymer may be 20%-30%, for example 24%-28%, for example 24.10%, 24.20%, 25.10%, 25.90% or 27.80%.
9. The composition for lithium battery according to claim 8, characterized in that: The composition also includes ceramic powder; Preferably, the composition satisfies one or more of the following conditions: (1) The ceramic powder is selected from one or more of aluminum oxide, boehmite, silicon oxide, titanium oxide, calcium carbonate, barium sulfate and magnesium oxide, such as aluminum oxide; (2) The mass ratio of the ceramic powder to the acrylic polymer is (15-25):1, such as 18:1, 19:1, 20:1 or 21:1; another example is 20:1; (3) The solid content of the composition is 10%-90%, such as 30%-50%, and further such as 39% or 41%; More preferably, the composition comprises a first component of water, a second component of water, the acrylic polymer and ceramic powder; or the composition comprises a first component of water, an aqueous solution of the acrylic polymer and ceramic powder; for example, the solid content of the composition is 41% or 39%; the mass ratio of the ceramic powder to the acrylic polymer is 20:1; Further preferably, the composition comprises the following components in parts by mass: 30-60 parts of ceramic powder, 6-12 parts of acrylic polymer aqueous solution and 40-90 parts of the first component water; More preferably, the composition satisfies one or more of the following conditions: (1) The mass fraction of the ceramic powder is 35 parts to 55 parts, for example, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts; (2) the weight percentage of the acrylic polymer aqueous solution is 7 parts to 11 parts, for example, 7 parts, 8 parts, 9 parts, 10 parts or 11 parts; (3) The mass fraction of the first component water is 50 parts to 85 parts, for example, 52.5 parts, 60 parts, 67 parts, 75 parts or 83 parts; (4) The mass ratio of the ceramic powder to the acrylic polymer aqueous solution is (3.2-7.8):1, for example, 5:1; Still more preferably, the composition is composed of the following components in parts by mass: 30-60 parts of ceramic powder, 6-12 parts of acrylic polymer aqueous solution and 40-90 parts of the first component water, wherein the acrylic polymer aqueous solution has a solid content of 20%-30%; Still more preferably, the composition is any of the following: Scheme 1: The composition is composed of the following components in parts by mass: 35 parts of ceramic powder, 7 parts of acrylic polymer aqueous solution and 52.5 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 24.10%; Scheme 2: The composition is composed of the following components in parts by mass: 45 parts of ceramic powder, 9 parts of acrylic polymer aqueous solution and 67 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 25.9%; Scheme 3: The composition is composed of the following components in parts by mass: 55 parts of ceramic powder, 11 parts of acrylic polymer aqueous solution and 83 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 24.2%; Scheme 4: The composition is composed of the following components in parts by mass: 40 parts of ceramic powder, 8 parts of acrylic polymer aqueous solution and 60 parts of the first component water; the acrylic polymer aqueous solution has a solid content of 27.8%; Solution 5: The composition consists of the following components in parts by mass: 50 parts of ceramic powder, 10 parts of an acrylic polymer aqueous solution and 75 parts of a first component of water, wherein the acrylic polymer aqueous solution has a solid content of 25.1%.
10. The composition for lithium battery according to claim 7, characterized in that: The composition comprises the acrylic polymer and ceramic powder; the mass ratio of the ceramic powder to the acrylic polymer and the definition of the ceramic powder are as described in claim 9; Preferably, the composition consists of the following components: the acrylic polymer and ceramic powder; More preferably, the composition is prepared by the following method, which comprises the following steps: mixing the following components in parts by mass and then drying to obtain the composition; the components comprise a first component of water, a second component of water, the acrylic polymer as described above, and a ceramic powder, or the components comprise a first component of water, an aqueous solution of an acrylic polymer, and a ceramic powder; the definitions of the water, the acrylic polymer, the aqueous solution of the acrylic polymer, and the ceramic powder are as described in claim 9; Most preferably, the composition is in the form of a film.